2007
DOI: 10.1007/s11934-007-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Male overactive bladder: The role of urodynamics and anticholinergics

Abstract: Millions of men suffer from overactive bladder and lower urinary tract symptoms. The adverse effects on quality of life and costs associated with the condition have been well described. In men, the pathophysiology of lower urinary tract symptoms may be from a number of causes including bladder outlet obstruction, detrusor overactivity, or both. Increasing data and clinical experience support the efficacy and safety of anticholinergics in men; the rate of urinary retention has been equal to that of placebo in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The International Consultation on Incontinence recommends pressure flow urodynamics in the evaluation of men when a precise diagnosis of BOO is important. 22 To our knowledge this is the only method that can differentiate men with a low peak flow rate due to detrusor underactivity from those with BOO.…”
Section: Discussionmentioning
confidence: 99%
“…The International Consultation on Incontinence recommends pressure flow urodynamics in the evaluation of men when a precise diagnosis of BOO is important. 22 To our knowledge this is the only method that can differentiate men with a low peak flow rate due to detrusor underactivity from those with BOO.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the electrical conductivity of polyacetylene (PA) could be significantly increased after doping with metal. [ 1–3 ] High conductivity mainly originated from the π electron migration, while it is restricted in most conjugated polymers due to the limited electrons transfer between π orbitals in the highly structured molecular chains. Introducing conductive heteroatoms into polymers can not only greatly improve their conductivity and redox activity by changing π orbitals and enhancing flexible electrons mobility on the molecular chain, [ 4–7 ] but also encourage the ability to capture and adsorb cations, improving the application potential.…”
Section: Introductionmentioning
confidence: 99%